Pengaruh Keragaman Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian di Kedai Kopi 372 Cimahi - Nazma , Rassel; Aksan , Prihartono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of product diversity and service quality on purchasing decisions at Kedai Kopi 372 Cimahi. The research uses quantitative methods. The research population was 50 people who were consumers of 372 coffee shops. The sample collection technique uses non-probability sampling techniques. The number of samples used was 50 people with a confidence level of 95%. Data testing uses SPSS V23. The data collection method used in this research is a questionnaire. The analytical methods used are validity tests, reliability tests, classical assumption tests consisting of normality tests, heteroscedasticity tests and multicollinearity tests, and multiple linear regression analysis consisting of determination analysis, F test and T test. The results of this test are partial. Product diversity does not have a significant impact on purchasing decisions, which means H1 is rejected. Service quality partially has a positive or significant impact on purchasing decisions, which means H2 is accepted. And simultaneously H3 is accepted, which means there is a positive and significant influence between product diversity and service quality on purchasing decisions.